A expressão do tempo no romance histórico: um estudo em Boca do Inferno de Ana Miranda - Azevedo, Ivete Monteiro de (2008)
This study explores the verbal temporality in Ana Miranda s novel Boca do Inferno, aiming at analyzing the verbal tense and its discoursive projection in the narrative text, in the light of a discoursive temporalization theory. From the establishment of an interface between the historical novel and History, we examine the installation of the time in the enunciation, the demarcation of the intervals of time in which the fact expressed by the verb is situated (simultaneity, anteriority and posteriority), as well as the correlation between tense, enunciate positioning and enunciative voice. In this novel, the questioning about the authority and about the objectiveness of the historical speech depends on the existence of this very speech which serves as its instrument. Boca do Inferno presents an ambivalent constitution: it resembles a biographical narrative (an account of the speech of the characters, of the life of the dissolute poet, Gregório de Matos) as much as a narrative history (historical event, historical recriation of the surroundings and of the colonial time), thus starting a duplicity in the speech of fiction and History. One of the relevant results is the realization of a disrupted structure between the perfect and the imperfect verbal tenses, which habitually express the narrated world. This disrupture, a reflection of this duplicity, starts an intentional argumentative strategy that causes, in the same narrative segment, a point of view displacement of the historiannarrator, codified in the past perfect tense, and that of the oniscient intruder-narrator, codified in the narrative imperfect tense: thus transverted, the narrator starts presenting subjective-critical commentaries, with a satirical tone, of the customs of the time and the city of Bahia, its insubordinations and its lewdness.